PELAKSANAAN PERJANJIAN SEWA- MENYEWA TERHADAP BARANG MILIK DAERAH YANG DILAKUKAN PEMERINTAH KABUPATEN KEDIRI DAN PD BPR BANK DAERAH KABUPATEN KEDIRI - Marzuki, Ismail; Nurbaedah, Nurbaedah (MIZAN, Jurnal Ilmu Hukum, 2025)
This study examines the implementation of lease agreements for regional assets between the Kediri District Government and the Regional Bank of Kediri District (PD BPR). The research method employed is socio-legal jurisprudence with descriptive analysis. Primary data includes Civil Code, Agrarian Law, and regulations, supplemented by secondary data from books, journals, and other documents. Data were collected through interviews and document studies. The findings indicate that lease agreements are conducted annually between the Kediri District Government and PD BPR Kediri District. The lease period is one year, with agreed-upon prices updated annually. The Kediri District Government proposes annual rent increases, which are negotiated and incorporated into the lease agreement. Land management is leased for public interest and regional revenue. The Kediri District Government grants the right to use land and buildings for a specific period without ownership rights. Lease agreements are renewed annually to determine rental prices. Ownership rights for school building construction remain with the Kediri District Government, with PD BPR Kediri District acting solely as a lessee.